A Simple Ceramic Water Filter for Water Purification in the Rural Area - Yusuf, Kamorudeen; Abadunmi, Taiwo; Adeola, Adewumi; Giegbefumwen, Samuel (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Most rural dwellers in Nigeria are living in areas where tap water are not available and they depend mainly on ponds and streams water for drinking which in most cases the water have been contaminated with pathogens, guinea-worm and agricultural waste products. This study was conducted to develop simple ceramic filters for purification of water. Two ceramic water filters were produced using kaolinite-clay and sawdust. Percentage compositions of sawdust to kaolinite-clay for the ceramic water filters by volume were 40%-60% (F1) and 50%-50% (F2). The Sawdust (from hardwood) and kaolinite-clay were ground and sieved through 0.075 mm sieve. The kaolinite-clay and sawdust were thoroughly mixed, soaked in water for 24 hours, mixed again and heated inside a furnace at 900-950°C for 8 hours. Each filter has 220mm diameter at the top, 180mm diameter at the bottom, 240mm in height and 20 in thickness. Water samples were collected after filtration and analyzed. The flow rate of F1 and F2 were 77 mL/h and 108 mL/h, respectively. Total coliform of raw water was 2.08 cfu/ml but total coliform was not detected after filtration through the two filters. The filters reduced water hardness, turbidity, Calcium, Chloride, Iron, Magnesium and Zinc from the water.